Nanoengineering of Temperature Sensitive Magnetic Fluids For Cooling Applications In Power Transformers - Kaur, Navjot (My University, 2019)
Transformers generate heat through energy losses and get heated due to iron core and copper losses that results into elevated resistance within the windings, increased hysteresis loss and decreased saturation magnetization of the core and degradation of the transformer’s insulation. Ultimately these will lead to significant and permanent efficiency reduction. Therefore, it is necessary to dissipate the heat generated by the core and windings so that the temperature of the transformer can be kept below a threshold at which the insulation begins to deteriorate. To inhibit temperature rise, transformers are cooled with mineral oils. The final, steady-state temperature of the transformer reflects equilibrium between power losses and heat dissipation properties of the coolant. As the oil is heats up, it experiences decrease in the density. Oil in contact with the transformer coils absorbs highest amount of heat and as a result it becomes least dense and starts rising relative to the surrounding oil. The rising oil makes contact with the walls of the housing, transfers heat to the walls and ultimately to the exterior environment. The cooled oil moves downward and replace the heated oil, which is rising from the windings. This natural convection caused by the interplay between the gravity and heat induced density variation represents the cooling mechanism most commonly utilized in commercial high power transformers. Gravitational forces that circulate oil in transformers are relatively weak. Temperature gradients across the oil reservoirs are often observed to be quite large, which results into poor heat transfer. Transformer windings frequently develop “hot spots” that can cause insulation break-down. These factors can lead to significant and permanent efficiency reduction. Development of coolants with enhanced thermal conductivity and better dielectric properties is critical for uninterrupted operation of high power transformers. Magnetic fluids can provide thermal and dielectric benefits over transformer oils. Magnetic fluids are colloidal suspensions of superparamagnetic nanoparticles coated with surfactant and dispersed in a carrier liquid. If used as a coolant, they can improve the cooling efficiency of transformers by enhancing the fluid circulation within windings because of the magnetically driven fluid flow. Magnetic field is present in the surroundings of windings and core of the transformer. This “leakage field‟ occurs because of electrical currents in the windings and reflects imperfect channeling of magnetic flux into the core. Its strength is highest in the immediate vicinity of the core and windings, and falls of rapidly with increasing distance. This magnetic field gradient draws magnetic fluid towards the core. Since the core and windings generate heat, the temperature of the fluid rises as it approaches towards the core, resulting into the loss of magnetic properties and decrease in density. The magnetic fluid starts rising as the gravitational effect of density reduction begins to overcome the weakening of magnetic attraction. Movement of hot magnetic fluid is assisted by the attraction exerted by the core and windings on cooler more intense magnetic fluid, which displaces the hot rising fluid as it travels toward the core. Movement away from the heat source and contact with the walls of the housing causes the hot magnetic fluid to cool and reacquire magnetization. This convection cycle, driven by the magnetic and gravitational forces, involves much faster fluid flow and therefore greater cooling efficiency can be achieved with natural convection. In addition, magnetic fluids can increase the transformer capacity to withstand lightning impulses, while minimizing the effect of moisture in typical insulating fluids. Magnetic nanoparticles can also minimize dielectric breakdown in transformers. Magnetization of magnetic fluid is temperature-dependent, decreasing steadily until the fluid reaches a characteristic “Curie temperature” at which, it loses all its magnetic strength. This property of temperature sensitive magnetic fluid can be exploit to design a smart coolant that can tune its cooling efficiency according to the operating temperature of the transformer by adjusting its magnetic field induced convective flow. These characteristics of magnetic fluid based coolant help in designing smaller, more efficient transformers, or to extend the life and loading capability of existing units. Despite of promising nature of this technology, very little efforts have been made to explore it. In our understanding the fundamental reason behind this is the inherent complexity involved in design and synthesis of stable, temperature sensitive magnetic fluids. Ferrites are generally used to prepare magnetic fluids. Most substituted ferrites tend to have Curie temperatures too high for practical use in the proposed application. However, many mixed and rare earth doped ferrites exhibit Curie temperatures in the range of 100 °C –300 °C. Among different temperature sensitive magnetic materials, Zn-containing spinel ferrites (Me1-xZnxFe2O4) are most attractive because they allow large variation in their magnetic properties with small variation in the Zn content. For transformer cooling applications, temperature sensitive magnetic fluids also needs to be stable under extreme conditions of temperature and magnetic field. This thesis provides an insight into the synthesis of stable temperature sensitive magnetic fluids with tunable Curie temperatures which are suitable for transformer cooling. Influence of particle size and size distribution on the colloidal stability of magnetic fluids and temperature induced aging of magnetic fluids is also the core focus of this thesis. The outcome of the doctoral research is organized in seven chapters. This thesis begins with the Introduction of magnetic fluids, in Chapter 1. It summarizes various properties and applications of magnetic fluids. The concept of temperature sensitive magnetic fluids is introduced for cooling applications in power transformers. It also evaluates potential magnetic nanoparticles that are well suited for thermo-magnetic cooling, on the basis of moderate saturation magnetization and tunable Curie temperature and discusses the unique properties of MZ ferrite based magnetic fluids. Chapter 2 summarizes existing literature on ferrite magnetic nanoparticles and their magnetic fluids. In the first section various methods developed for the synthesis of magnetic nanoparticles are reviewed. The focus of the literature review is to evolve correlation between synthesis conditions, particle size and their magnetic properties. In the second section, various techniques developed for the synthesis of magnetic fluids are reviewed. The focus here is on the correlation between tunable Curie temperature and saturation magnetization of fluids. In the third section of Chapter-2, literature on structural, magnetic and thermal properties of magnetic fluids are summarized. This chapter ends with discussion on stability and aging of magnetic fluids at elevated temperature. Chapter 3 provides details of experimental protocols developed and followed for the synthesis of MZ ferrite magnetic nanoparticles. In the first part of this chapter, synthesis of uniform MZ ferrite nanoparticles is carried out by chemical co-precipitation method. A series of Mn1-xZnxFe2O4 (x = 0 – 1) nanoparticles are synthesized by chemical co-precipitation method. Amongst them MZ nanoparticles with high saturation magnetization are used for further investigation. In the second part, a series of MZ nanoparticles are synthesized by co-precipitation method as a function of co-precipitation pH (10 – 13), reaction temperature (80 – 100 °C) and reaction time (1 – 4 h). The correlation between particle size and saturation magnetization have also been evaluated in this chapter. In Chapter 4, protocols for the synthesis of magnetic fluids with tunable Curie temperature and saturation magnetization are described. In this chapter, synthesis of MZ fluids having varying Zn content, an oleic acid as surfactant and commercial transformer oil as carrier liquid is explained. Magnetic properties of MZ fluids are analysed with modified Langevin theory. By fitting magnetization data with modified Langevin theory, magnetic particle diameter (Dm), saturation magnetization (Ms), polydispersity ( ), mean field constant () and ferrimagnetic susceptibility () are determined. Evaluation of effect of aging on the colloidal stability of magnetic fluids is studied in Chapter 5. This study was conducted over an extended period of 210 days. Photon Correlation Spectroscopy (PCS) and Vibrating Sample Magnetometry (VSM) are used to determine effect of aging on the colloidal stability and magnetic properties of MZ fluids. Chapter 6 aims to evaluate colloidal stability of magnetic fluids under accelerated thermal aging and its correlation with hydrodynamic size and magnetic properties of the magnetic fluids. In this chapter, effect of accelerated thermal aging on the dispersion stability and magnetic properties have been evaluated by photon correlation spectroscopy and vibration sample magnetometry, respectively on MZ fluids that are aged at 50 °C to 150 °C for 0 – 72 h. A correlation between hydrodynamic size of nanoparticles, its polydispersity and colloidal stability of fluids have been established. Effect of influence of degree of Zn substitution on the stability of MZ fluids under accelerated thermal aging has also been evaluated. Chapter 7 summarises important findings of this work and scope for the future work.
Keywords: Magnetic Fluid; Colloidal Stability; Thermal Aging; Ferrites; Curie Temperature